The mill. Series one [videorecording (DVD)] - McNulty, Matthew, 1982-; McNally, Kevin; Hayes, Kerrie; Sumpter, Donald, 1943- ([Publisher not identified], 2014)
Based on the extensive historical archive of Quarry Bank Mill in Cheshire and portraying the lives of real people, this powerful scripted drama series depicts Britain at a time when the industrial revolution is changing the country beyond recognition. In the 1830s, children as young as nine work twelve-hour shifts in the mills, and the new class of mill-owning families prosper. But the so-called 'white slaves of England' are about to take their lives into their own hands.